A waste slag-based road base material and a preparation method thereof
Patent Information
- Application Number
- CN202611297759.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
然而,在寒冷地区,道路基层材料需承受频繁的冻融循环作用,现有技术制备的废弃炉渣基层材料普遍存在抗冻性能不足的问题
[0024]1、通过硅烷偶联剂在集料表面化学键合形成致密疏水膜,并协同纳米二氧化硅物理填充孔隙,大幅降低集料吸水率,减少内部可冻水量,同时增强集料与结合料的界面粘结,从根本上提升抗冻耐久性。
Smart Images

Figure CN123003249A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lightweight building materials technology, specifically to a road base material based on waste slag and its preparation method. Background Technology
[0002] With the rapid advancement of industrial and infrastructure construction, the annual emissions of waste slag (including bottom ash and blast furnace slag) from coal-fired power plants and industrial boilers have been continuously increasing. Large quantities of slag are left to accumulate in the open for extended periods, not only occupying valuable land resources but also posing environmental pollution risks due to the soluble harmful components they contain, which can easily leach into soil and water bodies through rainwater. The harmless and resource-based utilization of slag has become an urgent environmental and resource issue. Meanwhile, road construction projects have a huge demand for aggregates. Traditional road base materials rely heavily on natural sand and gravel, but the over-exploitation of natural sand and gravel has led to ecological problems such as mountain destruction and soil erosion. Furthermore, high-quality natural aggregate resources are becoming increasingly scarce, necessitating the search for stable and readily available recycled aggregate alternatives. Waste slag, rich in oxides such as silicon and aluminum, possesses certain pozzolanic activity and mechanical property potential, and theoretically can be used as recycled aggregate in the preparation of road base materials, achieving the dual benefits of replacing waste with resources. However, in cold regions, road base materials need to withstand frequent freeze-thaw cycles, and existing waste slag base materials generally suffer from insufficient frost resistance. Summary of the Invention
[0003] The purpose of this invention is to provide a solution to the technical problems mentioned in the background section. The road base material prepared by this invention has excellent frost resistance.
[0004] To achieve the above objectives, the present invention provides the following technical solution:
[0005] A method for preparing road base material based on waste slag includes the following steps:
[0006] (1) The fine aggregate, medium aggregate and coarse aggregate obtained after crushing and screening the bottom ash of the coal-fired furnace are mixed, washed, soaked in saturated lime water and dried to obtain pretreated aggregate;
[0007] (2) Mix silane coupling agent, anhydrous ethanol and deionized water, add glacial acetic acid to adjust the pH value, stir and hydrolyze to obtain hydrolysate, then add nano silica and polycarboxylic acid to the hydrolysate, and disperse by ultrasonication to obtain composite modified liquid;
[0008] (3) Mix the pretreated aggregate with the composite modification liquid and stir to make the surface of the aggregate uniformly coated with the modification liquid, and then perform heat treatment to obtain the modified aggregate;
[0009] (4) Fly ash, slag powder, metakaolin and triethanolamine are ball-milled together to obtain an ultrafine admixture. The ultrafine admixture is then mixed with silicate cement to obtain a composite binder.
[0010] (5) Mix the modified aggregate with an aqueous solution containing dispersed graphene oxide to obtain a mixture. Add the composite binder and continue stirring. Then add an aqueous solution containing anhydrous calcium chloride, air-entraining agent, polyvinyl alcohol and sodium silicate, and stir thoroughly to obtain the road base material.
[0011] In this invention, the frost resistance of road base materials is improved synergistically from the following two aspects: Firstly, by regulating the synergistic effect of chemical coupling and physical filling, the source path of freeze-thaw damage is blocked from the essential level of the aggregate. Specifically, under acidic conditions, the silane coupling agent KH-550 is hydrolyzed to generate silanol groups. These groups undergo a dehydration condensation reaction with the hydroxyl groups exposed on the surface of the bottom slag aggregate to form strong Si-O-Si covalent bonds, constructing a network organic-inorganic composite film tightly attached to the surface of the aggregate. At the same time, the nano-silica in the modified liquid avoids agglomeration by the steric hindrance effect of the polycarboxylic acid dispersant and uniformly fills the open pores and microcracks on the surface of the slag, achieving pore sealing at the physical level. Subsequent heat treatment further promotes the condensation reaction of the coupling agent molecules, strengthens the film density, and the exposed amino groups (-NH2) of the film can form strong chemical adsorption with cement hydration products, improving the interfacial adhesion between the aggregate and the binder. The core cause of freeze-thaw damage is the stress generated by the expansion of water upon freezing inside the aggregate. This invention significantly reduces the water absorption rate of the aggregate and decreases the content of freezeable water inside through the dual effects of chemical film formation and pore filling by nanoparticles. At the same time, the dense film layer and the enhanced interfacial bonding can resist the damage of freeze-thaw stress to the aggregate itself and the aggregate-binder interface, fundamentally improving the freeze-thaw resistance of the aggregate and laying a solid foundation for the overall freeze-thaw resistance of the material.
[0012] On the other hand, the structural damage of the matrix during freeze-thaw cycles is addressed through a multi-mechanism approach involving nano-reinforcement, freezing point modulation, and stress buffering. Specifically, polycarboxylate superplasticizers utilize steric hindrance to effectively prevent graphene oxide (GO) from being degraded by Ca in the highly alkaline and high-calcium environment of cement. 2+Precipitation and aggregation ensure the uniform dispersion of GO's sheet-like nanostructures. GO serves as a nanotemplate for the growth of hydration products, inducing CSH and CASH gels to form ordered crystalline arrangements, significantly enhancing the matrix's microscopic toughness and structural integrity, and improving its resistance to frost heave stress. Secondly, an air-entraining agent directionally introduces closed microbubbles with diameters of 50-200 μm. These bubbles are uniformly distributed within the matrix; when pore water freezes and expands, the bubbles act as pressure buffers, absorbing expansion stress and preventing cracking due to stress concentration. Furthermore, anhydrous calcium chloride not only lowers the freezing point of pore water, reducing the amount of water freezing and frost heave at sub-zero temperatures, but also accelerates the cement hydration process, promoting rapid early strength gains. This allows the matrix to form a dense and stable structure before freeze-thaw cycles, reducing water intrusion channels. Through these actions, a frost-resistant system is constructed, incorporating nano-toughening, bubble buffering, and freezing point regulation. This effectively mitigates the repeated damage caused by freezing expansion and melting contraction during freeze-thaw cycles, significantly reducing strength and mass loss in the matrix and improving frost resistance.
[0013] Preferably, in step (1), the soaking time in saturated lime water is 1 to 3 hours.
[0014] Preferably, in step (2), the silane coupling agent is silane coupling agent KH-550.
[0015] Preferably, in step (2), the amount of nano-silica added is 0.5 to 2.0% of the total mass of the composite modified liquid.
[0016] Preferably, in step (3), the amount of composite modified liquid added is 2 to 5% of the mass of the pretreated aggregate.
[0017] Preferably, in step (4), the mass ratio of fly ash, slag powder, metakaolin, and cement is 30:(15-20):(5-8):(45-50).
[0018] Preferably, in step (5), the amount of graphene oxide added is 0.03 to 0.07% of the mass of the modified aggregate.
[0019] Preferably, in step (5), the amount of composite binder added is 12-15% of the mass of the mixture.
[0020] Preferably, in step (5), the mass ratio of polyvinyl alcohol to sodium silicate is 1:(4-6).
[0021] This invention discovered in experiments that the micro-hydrophobicity and dense surface of slag aggregate strongly repel cement paste rich in air-entraining agents, causing water in the paste to be squeezed to the interface between the aggregate and the matrix, forming an extremely thin "interfacial water film." This not only induces beneficial microbubbles to rupture and coalesce into large, harmful cavities at the interface, causing the bubbles to lose their original frost heave stress buffering capacity, but also causes this water film to freeze and expand first at sub-zero temperatures, triggering the matrix to peel off in sheets from the aggregate surface. This results in a sharp increase in the strength loss rate of the material during freeze-thaw cycles, leading to a decrease in overall frost resistance. To further solve this technical problem, this invention introduces cost-effective low-polymerization-degree polyvinyl alcohol (PVA) and sodium silicate into the mixing water. Specifically, firstly, the excellent surface activity of PVA instantly reduces the surface tension of the cement slurry to forcibly wet the slag surface. The numerous hydroxyl groups on its molecular chains form strong hydrogen bonds with the amino groups of the silane coupling agent on the aggregate surface, achieving strong anchoring of the slurry to the aggregate. Then, sodium silicate rapidly captures excess free water at the interface, not only reacting with calcium ions to generate early-strength hydrated calcium silicate gel, but also promoting inorganic cross-linking and solidification of the PVA molecular chains, generating a highly elastic organic-inorganic composite hydrogel in situ at the aggregate interface. This micron-scale gel network, like a highly absorbent sponge, completely absorbs the dangerous interfacial water film and firmly "freezes" and seals the originally easily aggregated micron-scale bubbles in the network structure. It successfully transforms the originally weak interface most prone to frost heave damage into a flexible anti-freeze defense line with both strong adhesion and stress buffering capacity, fundamentally eliminating the phenomenon of interface frost cracking and peeling, and achieving synergy of the above two systems at the micro level and a significant improvement in the frost resistance of road base materials.
[0022] A road base material based on waste slag is prepared by the method described above.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. A dense hydrophobic film is formed on the surface of the aggregate by chemical bonding through silane coupling agent, and the pores are physically filled by nano-silica, which greatly reduces the water absorption rate of the aggregate and the amount of internal freezeable water. At the same time, it enhances the interfacial bonding between the aggregate and the binder, fundamentally improving the freeze-thaw resistance and durability.
[0025] 2. Uniformly dispersed graphene oxide (GO) guides the orderly arrangement of hydration products to toughen the matrix. An air-entraining agent is used to introduce closed microbubbles to buffer frost heave stress. Anhydrous calcium chloride is used to lower the freezing point and accelerate early hydration, thus constructing a stable matrix structure that effectively resists freeze-thaw cycle damage.
[0026] 3. Low-polymerization-degree polyvinyl alcohol (PVA) and sodium silicate are introduced. The former strongly wets and anchors the hydrophobic aggregate surface, while the latter promotes PVA crosslinking and forms a highly elastic composite hydrogel in situ at the interface. This gel can completely absorb the dangerous interfacial water film and firmly lock in buffer bubbles, transforming the weak interface into a strong, highly buffered, and flexible defense line to prevent frost heave and peeling. Attached Figure Description
[0027] Figure 1 This is a SEM image of the surface of the road base material prepared in Example 1 of the present invention after molding and curing.
[0028] Figure 2 XPS images of the road base material prepared in Example 1 of this invention after molding and curing. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1
[0031] A method for preparing road base material based on waste slag includes the following steps:
[0032] (1) Take the bottom ash (total content of SiO2, Al2O3, and Fe2O3 ≥75%, loss on ignition ≤8%) discharged from a coal-fired power plant. After crushing with a jaw crusher and grading with a vibrating screen, collect fine aggregates with a particle size of 1-5 mm, medium aggregates with a particle size of 5-20 mm, and coarse aggregates with a particle size of 20-30 mm. Mix them evenly in a mass ratio of 35% fine aggregates, 35% medium aggregates, and 30% coarse aggregates. Put them into a stone washing machine and rinse them with industrial water until the water is clear. Then, immerse the wet aggregates completely in saturated lime water for 2.5 hours to remove acidic impurities and provide an alkaline environment. After immersion, filter out the aggregates and send them to a 105℃ forced-air drying oven to dry to constant weight. Take them out and cool them to obtain pretreated aggregates.
[0033] (2) Measure out silane coupling agent KH-550, anhydrous ethanol and deionized water and mix them in a volume ratio of 1:5:0.5. Add glacial acetic acid to adjust the pH value to 4.5 and hydrolyze for 30 min under magnetic stirring to obtain a transparent hydrolysate. Then, add 1.5% of nano silica and 0.2% of polycarboxylic acid dispersant to the hydrolysate, and place the mixture in an ultrasonic disperser. Disperse the mixture at 350W power for 20 min to obtain a uniformly dispersed composite modified solution.
[0034] (3) Place the pretreated aggregate in a mixer, weigh out 2.8% of the mass of the pretreated aggregate, and spray the composite modified liquid evenly on the surface of the aggregate during mixing using a high-pressure spray device. Continue mixing for 5 minutes to ensure that the modified liquid fully covers the aggregate. Then, take out the aggregate, spread it out, and put it in a 100℃ oven for heat treatment for 2 hours to allow the silane coupling agent to undergo a condensation reaction and solidify into a film, thus obtaining the modified aggregate.
[0035] (4) Weigh out 30 parts of Grade II fly ash, 19 parts of S95 grade slag powder, and 7 parts of metakaolin by weight, add 0.05% of triethanolamine grinding aid (based on the total mass of the three admixtures), and feed them together into a ball mill for ball milling until the specific surface area reaches 450 m². 2 / kg, to obtain ultrafine admixture. Then the ultrafine admixture was dry-mixed with 48 parts of 42.5 grade silicate cement in a gravity-free mixer for 10 minutes to obtain composite binder.
[0036] (5) By mass, 100 parts of modified aggregate were added to a forced mixer. 0.06 parts of graphene oxide (GO) were pre-dispersed in 4 parts of mixing water and added to the mixer to mix with the aggregate for 60 seconds to obtain a mixture. Then, composite binder (14% of the mixture mass) was added and mixing was continued for 90 seconds. Finally, 1.5 parts of anhydrous calcium chloride, 0.01 parts of sodium dodecyl sulfate air-entraining agent, 0.1 parts of low-polymerization degree polyvinyl alcohol (PVA), and 0.55 parts of sodium silicate were dissolved together in 3 parts of mixing water. This mixture was poured into the mixer and stirred thoroughly for 120 seconds. After discharge, a high-performance waste slag road base material was obtained.
[0037] Example 2
[0038] A method for preparing road base material based on waste slag includes the following steps:
[0039] (1) Take the bottom ash (total content of SiO2, Al2O3, and Fe2O3 ≥75%, loss on ignition ≤8%) discharged from a coal-fired power plant. After crushing with a jaw crusher and grading with a vibrating screen, collect fine aggregates with a particle size of 1-5 mm, medium aggregates with a particle size of 5-20 mm, and coarse aggregates with a particle size of 20-30 mm. Mix them evenly in a mass ratio of 35% fine aggregates, 35% medium aggregates, and 30% coarse aggregates. Put them into a stone washing machine and rinse them with industrial water until the water is clear. Then, immerse the wet aggregates completely in saturated lime water for 1.5 hours to remove acidic impurities and provide an alkaline environment. After immersion, filter out the aggregates and send them to a 105℃ forced-air drying oven to dry to constant weight. Take them out and cool them to obtain pretreated aggregates.
[0040] (2) Measure out silane coupling agent KH-550, anhydrous ethanol and deionized water and mix them in a volume ratio of 1:5:0.5. Add glacial acetic acid to adjust the pH value to 4.5 and hydrolyze for 30 min under magnetic stirring to obtain a transparent hydrolysate. Then, add 0.8% of nano silica and 0.2% of polycarboxylic acid dispersant by mass of the total composite modified liquid to the hydrolysate. Place the mixture in an ultrasonic disperser and ultrasonically disperse it for 20 min at 350W power to obtain a uniformly dispersed composite modified liquid.
[0041] (3) Place the pretreated aggregate in a mixer, weigh out 2.2% of the mass of the pretreated aggregate, and spray the composite modified liquid evenly onto the surface of the aggregate during mixing using a high-pressure spray device. Continue mixing for 5 minutes to ensure that the modified liquid fully covers the aggregate. Then, take out the aggregate, spread it out, and place it in a 100℃ oven for heat treatment for 2 hours to allow the silane coupling agent to undergo a condensation reaction and solidify into a film, thus obtaining the modified aggregate.
[0042] (4) Weigh out 30 parts of Grade II fly ash, 16 parts of S95 grade slag powder, and 6 parts of metakaolin by weight, add 0.05% of triethanolamine grinding aid (based on the total mass of the three admixtures), and feed them together into a ball mill for ball milling until the specific surface area reaches 450 m². 2 / kg, to obtain ultrafine admixture. Then the ultrafine admixture was dry-mixed with 46 parts of 42.5 grade silicate cement in a gravity-free mixer for 10 minutes to obtain composite binder.
[0043] (5) According to the mass fraction, 100 parts of modified aggregate were added to a forced mixer. 0.04 parts of graphene oxide (GO) were pre-dispersed in 4 parts of mixing water and added to the mixer to mix with the aggregate for 60 seconds to obtain a mixture. Then, composite binder (13% of the mass of the mixture) was added and mixing was continued for 90 seconds. Finally, 1.5 parts of anhydrous calcium chloride, 0.01 parts of sodium dodecyl sulfate air-entraining agent, 0.1 parts of low-polymerization degree polyvinyl alcohol (PVA) and 0.45 parts of sodium silicate were dissolved together in 3 parts of mixing water. This mixture was poured into the mixer and stirred thoroughly for 120 seconds. After discharge, a high-performance waste slag road base material was obtained.
[0044] Example 3
[0045] A method for preparing road base material based on waste slag includes the following steps:
[0046] (1) Take the bottom ash (total content of SiO2, Al2O3, and Fe2O3 ≥75%, loss on ignition ≤8%) discharged from a coal-fired power plant. After crushing with a jaw crusher and grading with a vibrating screen, collect fine aggregates with a particle size of 1-5 mm, medium aggregates with a particle size of 5-20 mm, and coarse aggregates with a particle size of 20-30 mm. Mix them evenly in a mass ratio of 35% fine aggregates, 35% medium aggregates, and 30% coarse aggregates. Put them into a stone washing machine and rinse them with industrial water until the water is clear. Then, immerse the wet aggregates completely in saturated lime water for 2 hours to remove acidic impurities and provide an alkaline environment. After immersion, filter out the aggregates and send them to a 105℃ forced-air drying oven to dry to constant weight. Take them out and cool them to obtain pretreated aggregates.
[0047] (2) Measure out silane coupling agent KH-550, anhydrous ethanol and deionized water and mix them in a volume ratio of 1:5:0.5. Add glacial acetic acid to adjust the pH value to 4.5 and hydrolyze for 30 min under magnetic stirring to obtain a transparent hydrolysate. Then, add 1.0% of nano silica and 0.2% of polycarboxylic acid dispersant to the hydrolysate, and place the mixture in an ultrasonic disperser. Ultrasonically disperse the mixture for 20 min at 350W power to obtain a uniformly dispersed composite modified solution.
[0048] (3) Place the pretreated aggregate in a mixer, weigh out 2.5% of the mass of the pretreated aggregate, and spray the composite modified liquid evenly on the surface of the aggregate during mixing using a high-pressure spray device. Continue mixing for 5 minutes to ensure that the modified liquid fully covers the aggregate. Then, take out the aggregate, spread it out, and put it in a 100℃ oven for heat treatment for 2 hours to allow the silane coupling agent to undergo a condensation reaction and solidify into a film, thus obtaining the modified aggregate.
[0049] (4) Weigh out 30 parts of Grade II fly ash, 18 parts of S95 grade slag powder, and 6.5 parts of metakaolin by weight, add 0.05% of triethanolamine grinding aid (based on the total mass of the three admixtures), and feed them together into a ball mill for ball milling until the specific surface area reaches 450 m². 2 / kg, to obtain ultrafine admixture. Then the ultrafine admixture was dry-mixed with 48 parts of 42.5 grade silicate cement in a gravity-free mixer for 10 minutes to obtain composite binder.
[0050] (5) By mass, 100 parts of modified aggregate were added to a forced mixer. 0.05 parts of graphene oxide (GO) were pre-dispersed in 4 parts of mixing water. The mixture was added to the mixer and stirred with the aggregate for 60 seconds to obtain a mixture. Then, composite binder (13.5% of the mixture mass) was added and stirred for another 90 seconds. Finally, 1.5 parts of anhydrous calcium chloride, 0.01 parts of sodium dodecyl sulfate air-entraining agent, 0.1 parts of low-polymerization degree polyvinyl alcohol (PVA), and 0.5 parts of sodium silicate were dissolved together in 3 parts of mixing water. This mixture was poured into the mixer and stirred thoroughly for another 120 seconds. After discharge, a high-performance waste slag road base material was obtained.
[0051] Example 4
[0052] A method for preparing road base material based on waste slag includes the following steps:
[0053] (1) Take the bottom ash (total content of SiO2, Al2O3, and Fe2O3 ≥75%, loss on ignition ≤8%) discharged from a coal-fired power plant. After crushing with a jaw crusher and grading with a vibrating screen, collect fine aggregates with a particle size of 1-5 mm, medium aggregates with a particle size of 5-20 mm, and coarse aggregates with a particle size of 20-30 mm. Mix them evenly in a mass ratio of 35% fine aggregates, 35% medium aggregates, and 30% coarse aggregates. Put them into a stone washing machine and rinse them with industrial water until the water is clear. Then, immerse the wet aggregates completely in saturated lime water for 3 hours to remove acidic impurities and provide an alkaline environment. After immersion, filter out the aggregates and send them to a 105℃ forced-air drying oven to dry to constant weight. Take them out and cool them to obtain pretreated aggregates.
[0054] (2) Measure out silane coupling agent KH-550, anhydrous ethanol and deionized water and mix them in a volume ratio of 1:5:0.5. Add glacial acetic acid to adjust the pH value to 4.5 and hydrolyze for 30 min under magnetic stirring to obtain a transparent hydrolysate. Then, add 2.0% of nano-silica and 0.2% of polycarboxylic acid dispersant to the hydrolysate, and place the mixture in an ultrasonic disperser. Disperse the mixture at 350W power for 20 min to obtain a uniformly dispersed composite modified solution.
[0055] (3) Place the pretreated aggregate in a mixer, weigh out 3% of the composite modification liquid equivalent to the mass of the pretreated aggregate, and spray it evenly on the surface of the aggregate during mixing using a high-pressure spray device. Continue mixing for 5 minutes to ensure that the modification liquid fully covers the aggregate. Then, take out the aggregate, spread it out, and put it in a 100℃ oven for heat treatment for 2 hours to allow the silane coupling agent to undergo a condensation reaction and solidify into a film, thus obtaining the modified aggregate.
[0056] (4) Weigh out 30 parts of Grade II fly ash, 20 parts of Grade S95 slag powder, and 8 parts of metakaolin by weight, add 0.05% of triethanolamine grinding aid (based on the total mass of the three admixtures), and feed them together into a ball mill for ball milling until the specific surface area reaches 450 m². 2 / kg, to obtain ultrafine admixture. Then the ultrafine admixture was dry-mixed with 50 parts of 42.5 grade silicate cement in a gravity-free mixer for 10 minutes to obtain composite binder.
[0057] (5) By mass, 100 parts of modified aggregate were added to a forced mixer. 0.07 parts of graphene oxide (GO) were pre-dispersed in 4 parts of mixing water. The mixture was added to the mixer and stirred with the aggregate for 60 seconds to obtain a mixture. Then, composite binder (15% of the mixture mass) was added and stirred for another 90 seconds. Finally, 1.5 parts of anhydrous calcium chloride, 0.01 parts of sodium dodecyl sulfate air-entraining agent, 0.1 parts of low-polymerization degree polyvinyl alcohol (PVA), and 0.6 parts of sodium silicate were dissolved in 3 parts of mixing water. This mixture was poured into the mixer and stirred thoroughly for another 120 seconds. After discharge, a high-performance waste slag road base material was obtained.
[0058] Example 5
[0059] A method for preparing road base material based on waste slag includes the following steps:
[0060] (1) Take the bottom ash (total content of SiO2, Al2O3, and Fe2O3 ≥75%, loss on ignition ≤8%) discharged from a coal-fired power plant. After crushing with a jaw crusher and grading with a vibrating screen, collect fine aggregates with a particle size of 1-5 mm, medium aggregates with a particle size of 5-20 mm, and coarse aggregates with a particle size of 20-30 mm. Mix them evenly in a mass ratio of 35% fine aggregates, 35% medium aggregates, and 30% coarse aggregates. Put them into a stone washing machine and rinse them with industrial water until the water is clear. Then, immerse the wet aggregates completely in saturated lime water for 1 hour to remove acidic impurities and provide an alkaline environment. After immersion, filter out the aggregates and send them to a 105℃ forced-air drying oven to dry to constant weight. Take them out and cool them to obtain pretreated aggregates.
[0061] (2) Measure out silane coupling agent KH-550, anhydrous ethanol and deionized water and mix them in a volume ratio of 1:5:0.5. Add glacial acetic acid to adjust the pH value to 4.5 and hydrolyze for 30 min under magnetic stirring to obtain a transparent hydrolysate. Then, add 0.5% of nano silica and 0.2% of polycarboxylic acid dispersant to the hydrolysate, and place the mixture in an ultrasonic disperser. Disperse the mixture at 350W power for 20 min to obtain a uniformly dispersed composite modified solution.
[0062] (3) Place the pretreated aggregate in a mixer, weigh out 2% of the composite modification liquid equivalent to the mass of the pretreated aggregate, and spray it evenly on the surface of the aggregate during mixing using a high-pressure spray device. Continue mixing for 5 minutes to ensure that the modification liquid fully covers the aggregate. Then, take out the aggregate, spread it out, and put it in a 100℃ oven for heat treatment for 2 hours to allow the silane coupling agent to undergo a condensation reaction and solidify into a film, thus obtaining the modified aggregate.
[0063] (4) Weigh out 30 parts of Grade II fly ash, 15 parts of S95 grade slag powder, and 5 parts of metakaolin by weight, add 0.05% of triethanolamine grinding aid (based on the total mass of the three admixtures), and feed them together into a ball mill for ball milling until the specific surface area reaches 450 m². 2 / kg, to obtain ultrafine admixture. Then the ultrafine admixture was dry-mixed with 45 parts of 42.5 grade silicate cement in a gravity-free mixer for 10 minutes to obtain composite binder.
[0064] (5) According to the mass fraction, 100 parts of modified aggregate were added to a forced mixer. 0.03 parts of graphene oxide (GO) were pre-dispersed in 4 parts of mixing water and added to the mixer to mix with the aggregate for 60 seconds to obtain a mixture. Then, composite binder (12% of the mass of the mixture) was added and mixing was continued for 90 seconds. Finally, 1.5 parts of anhydrous calcium chloride, 0.01 parts of sodium dodecyl sulfate air-entraining agent, 0.1 parts of low-polymerization degree polyvinyl alcohol (PVA), and 0.4 parts of sodium silicate were dissolved together in 3 parts of mixing water. This mixture was poured into the mixer and stirred thoroughly for 120 seconds. After discharge, a high-performance waste slag road base material was obtained.
[0065] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that step 2 is omitted and the composite modified liquid added in step 3 is replaced with an equal mass of water.
[0066] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that step 5 is omitted and graphene oxide, anhydrous calcium chloride and sodium dodecyl sulfate are not added as air-entraining agents.
[0067] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that low-polymerization degree polyvinyl alcohol and sodium silicate are not added in step 5.
[0068] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that low-polymerization degree polyvinyl alcohol is not added in step 5.
[0069] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that sodium silicate is not added in step 5.
[0070] Performance testing:
[0071] 1. Compressive Strength Test: According to the "Technical Specifications for Construction of Highway Pavement Base Course" (JTG / T F20-2015), the road base course materials prepared in each embodiment and comparative example were placed into 150mm×150mm×150mm cylindrical molds and formed using static pressure at 20MPa. The molds were then placed in a standard curing room (temperature 20±2℃, humidity ≥95%) for 24 hours before demolding, and standard curing continued for 7 days and 28 days. Before testing, the specimen surface was wiped dry and placed on a compression testing machine. Unconfined compressive strength testing was conducted at a loading rate of 1mm / min. Three parallel specimens were tested in each group, and the average value was taken as the final result. This index reflects the core mechanical bearing capacity of the material. The test results are shown in Table 1.
[0072] 2. Freeze-thaw resistance test: Referring to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T50082-2009), cylindrical specimens aged 28 days were taken. The initial mass of the specimen (accurate to 0.01g) was first weighed, and the initial compressive strength was tested. Then, a rapid freeze-thaw method was used: freezing at -20±2℃ for 4 hours, followed by thawing in water at 20±2℃ for 4 hours, completing one freeze-thaw cycle, for a total of 25 cycles. After the cycles, the surface moisture of the specimen was wiped dry, the remaining mass was weighed, and the compressive strength was tested. The strength loss rate was calculated as (initial strength - freeze-thaw strength) / initial strength × 100%, and the mass loss rate was calculated as (initial mass - freeze-thaw mass) / initial mass × 100%. This index directly evaluates the durability of the material in cold environments. The test results are shown in Table 1.
[0073] 3. Water Absorption Test: Samples cured for 28 days were dried to constant weight (m0), then completely immersed in clean water at 20±2℃ for 24 hours. After soaking, the samples were removed, the surface moisture was wiped dry with a damp towel, and the saturated water absorption mass m1 was measured. The water absorption rate was calculated using the formula: Water Absorption Rate = (m1-m0) / m0 × 100%. Three parallel samples were tested in each group, and the average value was taken. This indicator reflects the material's water and air permeability and is directly related to its frost resistance. The test results are shown in Table 1.
[0074] Table 1:
[0075] 7-day unconfined compressive strength (MPa) 28-day unconfined compressive strength (MPa) Strength loss rate (%) after 25 freeze-thaw cycles Mass loss rate (%) after 25 freeze-thaw cycles 24-hour water absorption rate (%) Example 1 5.6 11.2 3.3 1.2 3.2 Example 2 5.0 9.8 4.1 1.8 3.9 Example 3 5.4 10.6 3.7 1.4 3.5 Example 4 5.9 11.5 3.1 0.9 2.8 Example 5 4.8 9.1 4.5 2.1 4.5 Comparative Example 1 3.2 6.5 28.5 7.5 10.8 Comparative Example 2 3.8 7.3 22.3 5.8 8.5 Comparative Example 3 4.2 8.8 18.7 4.2 6.3 Comparative Example 4 4.0 8.2 12.2 3.5 5.7 Comparative Example 5 3.9 7.9 13.8 3.8 6.0
[0076] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing road base material based on waste slag, characterized in that, Includes the following steps: (1) The fine aggregate, medium aggregate and coarse aggregate obtained after crushing and screening the bottom ash of the coal-fired furnace are mixed, washed, soaked in saturated lime water and dried to obtain pretreated aggregate; (2) Mix silane coupling agent, anhydrous ethanol and deionized water, add glacial acetic acid to adjust the pH value, stir and hydrolyze to obtain hydrolysate, then add nano silica and polycarboxylic acid to the hydrolysate, and disperse by ultrasonication to obtain composite modified liquid; (3) Mix the pretreated aggregate with the composite modification liquid and stir to make the surface of the aggregate uniformly coated with the modification liquid, and then perform heat treatment to obtain the modified aggregate; (4) Fly ash, slag powder, metakaolin and triethanolamine are ball-milled together to obtain an ultrafine admixture. The ultrafine admixture is then mixed with silicate cement to obtain a composite binder. (5) Mix the modified aggregate with an aqueous solution containing dispersed graphene oxide to obtain a mixture. Add the composite binder and continue stirring. Then add an aqueous solution containing anhydrous calcium chloride, air-entraining agent, polyvinyl alcohol and sodium silicate, and stir thoroughly to obtain the road base material.
2. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (1), the soaking time in saturated lime water is 1 to 3 hours.
3. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (2), the silane coupling agent selected is silane coupling agent KH-550.
4. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (2), the amount of nano-silica added is 0.5 to 2.0% of the total mass of the composite modified liquid.
5. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (3), the amount of composite modified liquid added is 2 to 5% of the mass of the pretreated aggregate.
6. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (4), the mass ratio of fly ash, slag powder, metakaolin, and cement is 30:(15-20):(5-8):(45-50).
7. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (5), the amount of graphene oxide added is 0.03 to 0.07% of the mass of the modified aggregate.
8. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (5), the amount of composite binder added is 12-15% of the mass of the mixture.
9. The method for preparing road base material based on waste slag according to claim 1, characterized in that, In step (5), the mass ratio of polyvinyl alcohol to sodium silicate is 1:(4-6).
10. A road base material based on waste slag, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.